ADMINISTRATIVE PAYMENT SYSTEM BP3 ON SMP Negri Kedoya 197 - Dedi Irwanto (Jurnal Manajemen Informatika, 2010)
The development of increasingly sophisticated computers are very helpful indata processing still using manual systems. This often creates problems relating to the accuracyof the data resulted in delays in data processing.Information that is valuable information quickly and accurately. So needed a system ofcomputerization as a supporter. Payments Administration System BP3 On SMP Negri Kedoya197 is designed with the aim to obtain and process information quickly and accurately as well assecure data storage. So with the end result is useful in decision making.